The Social Segregation in I Know Why The Caged Bird Sings by Maya Angelou - Husna, Dwi (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2024)
This study examines social segregation in Maya Angelou's "I Know Why the Caged Bird Sings" through a sociological lens, employing the framework of the sociology of literature. The literature review explores three perspectives within this framework: sociology of the author, sociology of the society, and sociology of the reader. Using Angelou's novel as a case study, the research focuses on the racial discrimination and segregation faced by African Americans in the 1930s and 1940s, emphasizing the lasting impact of historical injustices.